2016
DOI: 10.1021/acsami.6b10146
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Based Systemic Glioma-Targeted Drug Delivery Enabled by All-d Peptides

Abstract: As the most aggressive brain tumor, chemotherapy of malignant glioma remains to be extremely challenging in clinic. The blood-brain barrier (BBB) and blood-brain tumor barrier (BBTB) are physiological and pathological barriers preventing therapeutic drugs from reaching the glioma region. In addition, vasculogenic mimicry (VM) formed by invasive glioma cells instead of endothelial cells and angiogenesis are very common in glioma, leading to the poor prognosis and recurrence of glioma. An ideal drug delivery sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 48 publications
(75 reference statements)
2
58
0
Order By: Relevance
“…Liu et al [5] demonstrated that VM-positive glioma patients have a poorer prognosis than patients with VM-negative gliomas. Ju et al [9], Huang et al [33], and Ying et al [34] proved that liposomes containing VM-targeting drugs improve anti-glioma therapy in orthotopic glioma-bearing nude mice. In agreement with the above findings, our in vitro and in vivo results showed that the destruction of VM formation by HOXA-AS2 knockdown impaired glioma malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [5] demonstrated that VM-positive glioma patients have a poorer prognosis than patients with VM-negative gliomas. Ju et al [9], Huang et al [33], and Ying et al [34] proved that liposomes containing VM-targeting drugs improve anti-glioma therapy in orthotopic glioma-bearing nude mice. In agreement with the above findings, our in vitro and in vivo results showed that the destruction of VM formation by HOXA-AS2 knockdown impaired glioma malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). The disappear of the characteristic peak of maleimide group at 6.8 ppm in the 1H-NMR spectra of all peptide-PEG3400-DSPE indicated the successful reaction 58 , 59 . Liposomes were prepared by the thin film hydration and extrusion method 60 .…”
Section: Methodsmentioning
confidence: 96%
“…Due to this structure, liposome is able to solubilize the insoluble drug molecules and prevent the loaded drug from the harsh physiological environment [8][9][10]. In addition, the surface of liposome can be modified to prolong the blood circulation time and/or target specific tissues [11][12][13][14][15]. With these abovementioned advantages, various liposome systems have been clinically approved [8,9,16].…”
Section: Introductionmentioning
confidence: 99%